Development of novel neutral pads containing hydroxyl monomers to improve SIARC substrate compatibility for directed self-assembly of diblock copolymers
By developing new crosslinkable quaternary copolymers and five-membered copolymers, the problem of dewetting defects of neutral layer materials on SiARC substrates is solved, the coating retention and self-assembly quality on SiARC substrates are improved, and the orientation is achieved Stability and pattern correction ability of self-assembly process.
Patent Information
- Application Number
- CN202380037606.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-03
- Filing Date
- 2023-04-28
- Publication Date
- 2024-12-13
AI Technical Summary
The existing neutral layer materials cause dehumidification defects on SiARC substrates, affecting the quality of the directional self-assembly process, especially the terpolymers used on SiARC substrates exhibit serious dehumidification problems on SiARC substrates.
A new crosslinkable tetramer and five-membered copolymer were developed, consisting of styrene, 4-vinylbenzocyclobutene, methyl methacrylate and 2-hydroxyethyl methacrylate or methyl methacrylate 4-hydroxyphenyl acrylate is composed of 4,4'-azobis(4-cyanopentanol) or 4,4'-azobis(4-cyanovaleric acid), and the addition of hydroxyl or carboxylic acid Ended groups are used to improve compatibility and crosslinkability with SiARC substrates.
The new copolymer significantly reduces the defects of the neutral coating, improves the coating retention and self-assembly quality on SiARC substrates, avoids dehumidification problems, and ensures the stability and pattern correction ability of the directional self-assembly process.
Smart Images

Figure CN119137168A_ABST
Abstract
Description
Field of the Invention
[0001] The present invention relates to a neutral layer pad composition for directed self-assembly processing.
[0002] background
[0003] The self-assembly of block copolymers is a method suitable for producing smaller and smaller patterned features for manufacturing microelectronic devices, wherein the critical dimension (CD) of features of about nanometer scale can be achieved. The self-assembly method is suitable for expanding the resolution capability of microlithography for repeating features such as contact holes or column arrays. In conventional photolithography methods, ultraviolet (UV) radiation can be used to expose to a photoresist layer coated on a substrate or a layered substrate via a mask. Positive or negative photoresists are useful, and these can also contain refractory elements (such as silicon) to be able to be developed without water by conventional integrated circuit (IC) plasma treatment. In positive photoresists, UV radiation transmitted through the mask causes a photochemical reaction in the photoresist, so that the exposed area is removed using a developer solution or by conventional IC plasma treatment. On the contrary, in negative photoresists, UV radiation transmitted through the mask causes the area exposed to the radiation to become more unremovable with a developer solution or by conventional IC plasma treatment. Integrated circuit features (such as gates, vias, or interconnects) are subsequently etched into the substrate or layered substrate, and the remaining photoresist is removed. When using conventional photolithography exposure methods, the feature size of integrated circuit features is limited. Due to limitations on aberrations, focusing, proximity effects, minimum achievable exposure wavelengths, and maximum achievable numerical apertures, it is difficult to achieve further reductions in pattern size by radiation exposure. The demand for large-scale integration has led to continued reductions in circuit size and features in devices. In the past, the final resolution of features has depended on the wavelength of light used to expose photoresists, which has its own limitations. Directed (also referred to as guided) self-assembly techniques (e.g., graphoepitaxy and chemoepitaxy using block copolymer imaging) of patterned regions on application substrates are highly desirable techniques for improving resolution while reducing CD variations. These techniques can be applied to enhance conventional UV lithography or to achieve even higher resolution and CD control in methods using EUV, electron beams, deep UV, or immersion lithography. Directed self-assembly block copolymers include blocks of etch-resistant copolymer units and blocks of highly etchable copolymer units, which, when coated, aligned, and etched on a substrate, produce regions with extremely high density patterns.
[0004] For the directional (guiding) or non-guided self-assembly of the block copolymer film on the patterned or non-patterned substrate area respectively, the self-assembly method of this block polymer layer usually occurs during the annealing of this film covered on the neutral layer. This neutral layer above the semiconductor substrate can be an unpatterned neutral layer, or in chemical epitaxy or graphic epitaxy, this neutral layer can contain graphic epitaxy or chemical epitaxy guiding features (formed by UV lithography as described above) respectively. During the annealing of the block copolymer film, the bottom neutral layer guides the nano-phase separation of the block copolymer domain. An example is to form a phase-separated domain, which is a thin layer or cylinder perpendicular to the bottom neutral layer surface. These nano-phase separation block copolymer domains form pre-patterns (such as lines and gaps L / S), which can be transferred to the substrate by etching methods (such as plasma etching). In graphic epitaxy or in chemical epitaxy, these guiding features can indicate both pattern rectification (pattern rectification) and pattern multiplication. In the case of an unpatterned neutral layer, this produces a repeating array of, for example, L / S or CH. For example, in conventional block copolymers such as poly(styrene-b-methyl methacrylate (P(Sb-MMA)) where the two blocks have similar surface energies at the BCP-air interface, this can be achieved by coating the block copolymer on a layer of non-preferential or neutral material grafted or crosslinked at the polymer-substrate interface and thermally annealing it.
[0005] In the pattern epitaxy directed self-assembly method, block copolymers self-organize around a substrate pre-patterned using conventional photolithography (ultraviolet, deep UV, electron beam, extreme UV (EUV) exposure light source) to form repeating topographical features, such as line / space (L / S) or contact hole (CH) patterns. In one example of L / S directed self-assembled arrays, block copolymers can form self-aligned lamellar regions that can form parallel line-space patterns of different spacings in the grooves between the pre-patterned lines, thereby improving pattern resolution by subdividing the gaps in the grooves between the topographic lines into finer patterns. For example, diblock copolymers or triblock copolymers that are capable of microphase separation and contain blocks rich in carbon (such as styrene or containing some other elements, such as Si, Ge, Ti) that are resistant to plasma etching and blocks that are highly plasma etchable or removable can provide high-resolution pattern definition. Examples of highly etchable blocks can include monomers that are rich in oxygen and free of refractory elements and that are capable of forming highly etchable blocks, such as methyl methacrylate. The plasma etching gas used for the etching process of defining the self-assembled pattern is generally those gases used in the method for manufacturing integrated circuits (ICs). In this way, extremely fine patterns other than those defined by conventional photolithography can be produced in a typical IC substrate, thereby achieving pattern multiplication. Similarly, features such as contact holes can be made denser by using graphic epitaxy, in which suitable block copolymers are arranged by directed self-assembly around the contact holes or column arrays defined by conventional photolithography, thereby forming a denser array of etchable domains and etching-resistant domains, which produce a denser array of contact holes when etching. Therefore, graphic epitaxy has the potential to provide both pattern correction and pattern multiplication.
[0006] In chemical epitaxy or pinning chemical epitaxy, the self-assembly of block copolymers is formed on the surface of the region whose guiding feature is different chemical affinity, and the surface does not have or has no significant morphology (also called non-guided morphology) indicating the directed self-assembly process. For example, the surface of the substrate can be patterned using conventional photolithography (UV, deep UV, electron beam, EUV) to produce a surface of different chemical affinity in a line and gap (L / S) pattern, wherein the exposed area where the surface chemistry has been modified by radiation alternates with the unexposed area and does not show chemical changes. There is no morphological difference in these areas, but there is a surface chemical difference or pinning to the directed self-assembly of the block copolymer fragments. Specifically, the directed self-assembly of the block copolymer whose block fragments contain etching-resistant repeating units (such as styrene repeating units) and fast etching repeating units (such as methyl methacrylate repeating units) will allow the etching-resistant block fragments and highly etchable block fragments to be accurately placed above the pattern. This technology allows these block copolymers to be accurately placed after plasma or wet etching treatment and the subsequent pattern transfer of the pattern to the substrate. The advantage of chemical epitaxy is that it can be finely tuned through changes in chemical differentiation to help improve line-edge roughness and CD control, thus allowing pattern correction. Other types of patterns, such as repeating contact hole (CH) arrays can also be pattern corrected using chemical epitaxy.
[0007] These neutral layers are layers on the surface of substrates or treated substrates, which do not have affinity for any of the block segments of the block copolymers used in directional self-assembly. In the graphic epitaxy method of directional self-assembly (DSA) of block copolymers, neutral layers are used because they allow the correct placement or orientation of the block polymer segments for directional self-assembly, which allows the etching-resistant block polymer segments and highly etchable block polymer segments to be correctly placed relative to the substrate. For example, in the surface containing the line and gap features defined by conventional radiation lithography, the neutral layer allows the block segments to be oriented so that the block segments are oriented perpendicular to the surface of the substrate, depending on the length of the block segments in the block copolymer, such as related to the length between the lines defined by conventional photolithography, which is ideal for pattern correction and pattern multiplication. If the substrate interacts too strongly with one of the block segments, it will cause the segment to be located flat on the surface of the substrate to maximize the contact surface between the segment and the substrate; this surface will interfere with the required vertical alignment that can be used to realize pattern correction or pattern multiplication based on the features generated by conventional photolithography. Tailoring the selected smaller area or pinning substrate so that it interacts strongly with one block of the block copolymer, and coating the rest of the surface with a neutral layer can be useful for forcing the domains of the block copolymer to align in a desired direction, and is the basis for pinned chemoepitaxy or graphic epitaxy for pattern multiplication. The pinning region can be a hydrophilic region that has a greater affinity for, for example, polar block copolymer segments such as polymethyl methacrylate block segments in a block copolymer of styrene and methyl methacrylate, or a hydrophobic pinning region that has a greater affinity for, for example, polystyrene block segments in a block copolymer of styrene and methyl methacrylate.
[0008] Directed self-assembly using PS-b-PMMA type block copolymers requires a neutral bottom layer for chemical epitaxy growth of line and gap patterns, which can work on many different types of substrates. Crosslinkable terpolymers such as P(Sr-VBCB-r-MMA) (i.e. poly(styrene-to-4-vinylbenzocyclobutene-to-methyl methacrylate)) have been used as crosslinked neutral pad compositions in DSA methods. This terpolymer works effectively as a neutral layer on oxide and nitride substrates such as SiNyOx (silicon oxynitride) and SiN (silicon nitride), but due to its hydrophobicity, this terpolymer causes severe dewetting (de-wetting) defects on SiARC (silicon anti-reflective coating) substrates, resulting in defects in subsequent DSA methods. Therefore, it is necessary to develop a new crosslinkable neutral pad material that is particularly suitable for SiARC substrates.
[0009] Detailed description with drawings
[0010] Figure 1:P(Sr-VBCB-r-MMA-r-HEMA)-OH-Representative NMR Example 1
[0011] Figure 2 :P(Sr-VBCB-r-MMA-r-PQMA)-OH-Representative NMR Example 5
[0012] Figure 3 : Defectivity of neutral layer coatings derived from P(Sr-VBCB-r-MMA-r-HEMA)-OH and P(Sr-VBCB-r-MMA-r-PQMA)-OH compared to reference materials
[0013] Figure 4 :SEM image evaluation of neutral layer coating on SiARC
[0014] Figure 5 : Comparison of defects in the self-assembled structures of Examples 1 and 5 compared to Comparative Example 1 on ISX-302
[0015] Figure 6 : Evaluation of SEM images of self-assembled structures
[0016] Figure 7 : Comparison of defects in the self-assembled structures of Examples 1 and 5 compared to Comparative Example 1 on ISX-304 Summary of the invention
[0017] A specific aspect of the present invention is an improved form of crosslinkable neutral tetrapolymers and pentapolymers that are compatible with SiARC and SiOx, SiNyOx and SiN substrates. In one aspect, the new tetrapolymer is composed of styrene (S), 4-vinylbenzocyclobutene (VBCB), methyl methacrylate (MMA) and 2-hydroxyethyl methacrylate (HEMA) or 4-hydroxyphenyl methacrylate (PQMA), which is initiated by 4,4'-azobis(4-cyanopentanol) (AIBN-OH) or 4,4'-azobis(4-cyanovaleric acid) (AIBN-COOH). The S and MMA components impart the necessary neutrality to the polymer. The VBCB component allows the polymer to crosslink into an insoluble film when baked. The HEMA or PQMA component makes the polymer more compatible with SiARC substrates. The hydroxyl- or carboxylic acid-terminated end groups from the initiator graft the polymer to the substrate and maintain the polymer when the high temperature baking crosslinks the polymer.
[0018] In a broader aspect, the invention describes a random polymer having structure (A) comprising:
[0019] ·Styrene repeating units of structure (I), wherein R m1is H or C-1 to C-4 alkyl, R 1 is selected from H, C-1 to C-8 alkyl and C-1 to C-4 alkyloxy, and n1 is the total number of such repeating units; wherein in the copolymer, such repeating units are in the range of about 10 mol% to about 60 mol%;
[0020] · A repeating unit derived from 4-vinylbenzocyclobutene of structure (II), wherein R m2 is H or C-1 to C-4 alkyl, R 2 is H or C-1 to C-8 alkyl, and n2 is the total number of such repeating units; wherein in the copolymer, such repeating units are from about 15 mol% to about 35 mol%;
[0021] Repeating units derived from alkyl acrylate or alkyl 2-methylene alkanoate of structure (III), wherein R m3 is H or C-1 to C-4 alkyl, R 3 is a C-1 to C-8 alkyl group, and n3 is the total number of repeating units; wherein in the copolymer, the repeating unit is about 15 mol% to about 55 mol%;
[0022] - A hydroxy substituted acrylate or 2-methylene alkanoate derived repeating unit of structure (IV) present at about 1 mol % to greater than 5 mol %, wherein R m4 is H or C-1 to C-4 alkyl, R 1 is a C-1 to C-8 alkyl group, L 1 is a spacer moiety selected from a C-2 to C-12 alkylene spacer and a 1,4-phenylene spacer, wherein the alkylene spacer is selected from a C-2 to C-12 straight chain alkylene, a C-3 to C-12 branched chain alkylene, a C-3 to C-12 cyclic alkylene, and a C-5 to C-12 alicyclic alkylene, wherein there are at least two carbon atoms between the carbonyloxy moiety and the OH moiety, and the two moieties are independently attached to the alkylene spacer at different positions, the different positions being primary or secondary carbons on the alkylene moiety, and wherein the 1,4-phenylene spacer is a spacer in which the carboxyloxy moiety and the OH moiety are located at 1,4 positions relative to each other, and n4 is the total number of such repeating units;
[0023] As shown in structure (A), one of the two terminal groups is H and the other is Rr, Rr 1 and Rr 2 A substituted methyl moiety, wherein Rr 1 is a C-1 to C-8 alkyl group, Rr 2 selected from C-1 to C-8 alkyl, C-1 to C-8 alkylene hydroxyl moiety (-alkylene-OH), C-1 to C-8 alkylene carboxylic acid moiety (-alkylene-CO2 H), or a moiety of structure (B) comprising benzyl alcohol, wherein ni is an integer in the range of 0 to 5, nia is an integer in the range of 1 to 5, nib is an integer in the range of 1 to 5, and "*" indicates the point of attachment of this moiety, Rr is a cyano moiety (-CN) or a carbonylalkyl moiety (-C(=O)-Ri), wherein Ri is a C-1 to C-8 alkyl or aryl moiety; and further
[0024] wherein the sum of the individual mole % of repeating units of structures (I), (II), (III) and (IV) is less than or equal to 100 mole % of the total repeating units present in the copolymer.
[0025]
[0026] Another aspect of the invention is a composition comprising one of these polymers and an organic spin-coating solvent.
[0027] Another aspect of the invention is a method of coating these compositions and thermally producing a crosslinked neutral MAT layer and using this layer in a photolithographic DSA process. In the context of the present invention, a MAT layer is a crosslinked layer that is insoluble in any layer coated thereon and can be used as a DSA neutral or pinning layer.
[0028] DETAILED DESCRIPTION OF THE INVENTION
[0029] It should be understood that both the foregoing general description and the following detailed description are illustrative and explanatory and are not restrictive to the subject matter claimed. In this application, the use of the singular includes the plural, the word "a" or "an" means "at least one", and the use of "or" means "and / or", unless otherwise specifically stated. In addition, the use of the term "include" and other forms such as "include" and "included" is not restrictive. In addition, terms such as "element" or "component" cover both elements and components containing one unit and elements or components containing more than one unit, unless otherwise specifically stated. As used herein, the conjunction "and" is intended to be inclusive, and the conjunction "or" is not intended to be exclusive, unless otherwise stated. For example, the phrase "or, alternatively" is intended to be exclusive. As used herein, the term "and / or" refers to any combination of the aforementioned elements, including the use of a single element.
[0030] The term "C-1 to C-4 alkyl" represents methyl and C-2 to C-4 straight chain alkyl and C-3 to C-4 branched chain alkyl moieties, for example as follows: methyl (-CH 3 ), ethyl (-CH 2 -CH 3 ), n-propyl (-CH 2 -CH 2 -CH 3), isopropyl (-CH(CH 3 ) 2 、n-butyl (-CH 2 -CH 2 -CH 2 -CH 3 ), tert-butyl (-C(CH 3 ) 3 ), isobutyl (CH 2 -CH(CH 3 ) 2 , 2-butyl (-CH(CH 3 )CH 2 -CH 3 Similarly, the term C-1 to C-12 represents methyl, C-2 to C-12 straight chain, C-3 to C-12 branched alkyl, C-4 to C-12 cycloalkyl (e.g., cyclopentyl, cyclohexyl, etc.), or C-5 to C-12 alkylene cycloalkyl (e.g., -CH 2 -cyclohexyl, CH 2 -CH 2 -cyclopentyl, etc.).
[0031] The term "C-2 to C-12 alkylene" represents a C-2 to C-12 straight chain alkylene moiety (e.g., ethylene, propylene, etc.), a C-2 to C-12 branched chain alkylene moiety (e.g., -CH(CH 3 )-、-CH(CH 3 )-CH 2 -, etc.), C-5 to C-12 cyclic alkylene moieties (e.g., 1,4-cyclohexyl, 1,3-cyclopentyl, etc.), and C-5 to C-12 alicyclic (e.g., 2,6-adamantane-2,4-diyl, adamantane-2,6-diyl).
[0032] Diblock and triblock copolymers of styrene and 2-methylene alkanoic acid alkyl ester derived repeating unit moieties suitable for use as components in the inventive compositions described herein can be prepared by a variety of methods (e.g., anionic polymerization, atom transfer radical polymerization (ATRP), reversible addition-fragmentation chain transfer polymerization (RAFT) polymerization, living radical polymerization, etc.) (Macromolecules 2019, 52, 2987-2994; Macromol. Rapid Commun. 2018, 39, 1800479; A. Deiter Shluter et al., Synthesis of Polymers, 2014, Vol. 1, p. 315; Encyclopedia of Polymer Science and Technology, 2014, Vol. 7, p. 625).
[0033] The random copolymer poly(styrene-co-methyl methacrylate) is abbreviated as "P(S-co-MMA)" and the oligomeric form of this material is abbreviated as oligo(S-co-MMA). Similarly, the block copolymer poly(styrene-block-methyl methacrylate) is abbreviated as P(Sb-MMA) and the oligomer of this material is abbreviated as oligo(Sb-MMA). The oligomer oligo(styrene-co-p-octylstyrene)-block-(methyl methacrylate-co-di(ethylene glycol)methyl ether methacrylate) uses the same abbreviation to represent the random block copolymer element, specifically oligo(S-co-p-OS)-bP(MMA-co-DEGMEMA) where S = styrene, p-OS = p-octylstyrene, MMA = methyl methacrylate, DEGMEMA = di(ethylene glycol)methyl ether methacrylate, indicating that the two blocks are repeating units in this block copolymer that are random copolymers.
[0034] FOV is an abbreviation for "Field of View" of a top-down scanning electron micrograph (SEM) of the SEM images in this application. "L / S" is an abbreviation for "Line and Space" lithographic features.
[0035] PGMEA and PGME are abbreviations for 1-methoxypropan-2-yl acetate and 1-methoxypropan-2-ol, respectively.
[0036] The section headings used herein are for organizational purposes and shall not be construed as limiting the subject matter described. All documents or portions of documents cited in this application, including but not limited to patents, patent applications, articles, books, and papers, are hereby expressly incorporated herein by reference in their entirety for any purpose. In the event that one or more incorporated references and similar materials define a term in a manner inconsistent with the definition of that term in this application, the present application controls.
[0037] Unless otherwise indicated, "alkyl" refers to a hydrocarbon group that can be straight chain, branched (e.g., methyl, ethyl, propyl, isopropyl, tert-butyl, etc.), or cyclic (e.g., cyclohexyl, cyclopropyl, cyclopentyl, etc.), polycyclic (e.g., norbornyl, adamantyl, etc.). These alkyl moieties may be substituted or unsubstituted as described below. The term "alkyl" refers to such a moiety having C-1 to C-8 carbons. It should be understood that for structural reasons, straight chain alkyls start with C-1, while branched and straight chains start with C-3 and polycyclic alkyls start with C-5. In addition, it should be further understood that, unless otherwise indicated, moieties derived from alkyls described below (e.g., alkoxy and perfluoroalkyl) have the same carbon number range. If the length of the alkyl group is specified to be different from that described above, the alkyl definition described above still holds true with respect to its inclusion of all types of alkyl moieties as described above, and structural considerations regarding the minimum carbon number of a given type of alkyl group still apply.
[0038] Alkyloxy (also known as Alkoxy) refers to an alkyl group attached through an oxy (-O-) moiety (e.g., methoxy, ethoxy, propoxy, butoxy, 1,2-isopropoxy, cyclopentyloxy, cyclohexyloxy, etc.). These alkyloxy moieties may be substituted or unsubstituted as described below.
[0039] Halo or halogen refers to a halogen, F, Cl, Br or I, attached to an organic moiety through a bond.
[0040] As used herein, the term lactone encompasses both monolactones (eg, caprolactone) and dilactones (eg, lactide).
[0041] Haloalkyl refers to a linear, cyclic or branched saturated alkyl group such as defined above, wherein if more than one halo moiety is present, at least one of the hydrogens has been replaced by a halo selected from F, Cl, Br, I or mixtures thereof. Fluoroalkyl is a specific subgroup of these moieties.
[0042] Perfluoroalkyl refers to a straight chain, cyclic or branched saturated alkyl group as defined above in which hydrogen has been completely replaced by fluorine (eg, trifluoromethyl, perfluoroethyl, perfluoroisopropyl, perfluorocyclohexyl, etc.).
[0043] Copolymer of structure (A)
[0044] The present invention describes a random polymer having structure (A) comprising:
[0045] ·Styrene repeating units of structure (I), wherein R m1 is H or C-1 to C-4 alkyl, R 1 selected from H, C-1 to C-8 alkyl and C-1 to C-4 alkyloxy, n1 is the total number of such repeating units; wherein in the copolymer, such repeating units are in the range of about 10 mol% to about 60 mol%;
[0046] · A repeating unit derived from 4-vinylbenzocyclobutene of structure (II), wherein R m2 is H or C-1 to C-4 alkyl, R 2 is H or C-1 to C-8 alkyl, and n2 is the total number of such repeating units; wherein in the copolymer, such repeating units are from about 15 mol% to about 35 mol%;
[0047] Repeating units derived from alkyl acrylate or alkyl 2-methylene alkanoate of structure (III), wherein R m3 is H or C-1 to C-4 alkyl, R 3 is a C1 to C8 alkyl group, and n3 is the total number of such repeating units; wherein in the copolymer, such repeating units are from about 15 mol% to about 55 mol%;
[0048] · Repeating units derived from hydroxy-substituted acrylate or 2-methylene alkanoate of structure (IV), n4 is the total number of such repeating units; wherein R m4 is H or C-1 to C-4 alkyl, R I is a C-1 to C-8 alkyl group, L 1 is a spacer group portion selected from a C-2 to C-12 alkylene spacer group and a 1,4-phenylene spacer group, wherein the alkylene spacer group is selected from a C-2 to C-12 straight chain alkylene group, a C-3 to C-12 branched chain alkylene group, a C-3 to C-12 cyclic alkylene group, and a C-5 to C-12 alicyclic alkylene group, wherein there are at least two carbon atoms between the carbonyloxy moiety and the OH moiety, and the two moieties are independently attached to the alkylene spacer group at different positions, the different positions being primary carbons or secondary carbons on the alkylene moiety, and wherein the 1,4-phenylene spacer group is a spacer group in which the carboxyloxy moiety and the OH moiety are located at 1,4 positions relative to each other, and
[0049] wherein the repeating unit is from about 1 mol % to about 5 mol %;
[0050] As shown in structure (A), one of the two terminal groups is H and the other is Rr, Rr 1 and Rr 2 A substituted methyl moiety, wherein Rr 1 is a C-1 to C-8 alkyl group, Rr 2 selected from C-1 to C-8 alkyl, C-1 to C-8 alkylene hydroxyl moiety (-alkylene-OH), C-1 to C-8 alkylene carboxylic acid moiety (-alkylene-CO 2 H), or a moiety of structure (B) comprising benzyl alcohol, wherein ni is an integer in the range of 0 to 5, nia is an integer from 1 to 5, nib is an integer from 1 to 5, and "*" indicates the point of attachment of this moiety, Rr is a cyano moiety (-CN) or a carbonylalkyl moiety (-C(=O)-Ri), wherein Ri is a C-1 to C-8 alkyl or aryl moiety; and further
[0051] wherein the sum of the individual mole % of repeating units of structures (I), (II), (III) and (IV) is less than or equal to 100 mole % of the total repeating units present in the copolymer.
[0052]
[0053] In one aspect of the copolymer of structure (A) described herein, it is a copolymer whose repeating units consist of repeating units of structures (I), (II), (III) and (IV), wherein the sum of these repeating units is equal to 100 mole % of the repeating units in this copolymer.
[0054] In another aspect of the copolymers of structure (A) described herein, L 1 is the C-2 to C-12 alkylene spacer group.
[0055] In another aspect of the copolymers of structure (A) described herein, L 1 It is a 1,4-phenylene moiety spacer group.
[0056] In one aspect of the copolymers of structure (A) described herein, wherein L 1 is the C-2 to C-12 alkylene spacer group having a composition wherein the repeating units of structure (I) are from about 13 mol % to about 48 mol %, the repeating units of structure (II) are from about 25 mol % to about 35 mol %, the repeating units of structure (III) are from about 15 mol % to about 55 mol %, the repeating units of structure (IV) are from about 1 mol % to about 2 mol %, and the sum of the individual mole % of the repeating units of structures (I), (II), (III) and (IV) is equal to 100 mol % of the total repeating units in the copolymer.
[0057] In one aspect of the copolymers of structure (A) described herein, the repeating units of structure (IV), L 1 is the alkylene spacer group, and the repeating unit is selected from the repeating unit having structure (IVa1), structure (IVa2), structure (IVa3), structure (IVa4) or structure (IVa5), wherein x is an integer from 1 to 11, x1 is an integer from 1 to 8, x2 is an integer from 1 to 8, x3 is an integer from 1 to 2, x3a is an integer from 1 to 3, and R x1 is a C-1 to C-4 alkyl group, R x2 is a C-1 to C-4 alkyl group, and in the repeating unit of structure (IVa5), the substituent R x4 or R x5In another aspect of this embodiment, the repeating unit of structure (IV) has structure (IVa1). In another aspect of this embodiment, the repeating unit of structure (IV) has structure (IVa2). In another aspect of this embodiment, the repeating unit of structure (IV) has structure (IVa3). In another aspect of this embodiment, the repeating unit of structure (IV) has structure (IVa4). In another aspect of this embodiment, the repeating unit of structure (IV) has structure (IVa5). In another aspect of this embodiment, the repeating unit of structure (IV) has structure (IVa41). In another aspect of this embodiment, it more specifically has structure (IVa41). In another aspect of this embodiment, it has structure (IVa42). In another aspect of this embodiment, it has structure (IVa43). In another aspect of this embodiment, it has structure (IVa51). In another aspect of this embodiment, it has structure (IVa52).
[0058]
[0059]
[0060] In one aspect of the repeating unit of structure (IVa1) above, x is an integer from 2 to 11; in another aspect, x is an integer from 3 to 11; in another aspect, x is an integer from 4 to 11; in another aspect, x is an integer from 5 to 11; in another aspect, x is an integer from 6 to 11; in another aspect, x is an integer from 7 to 11; in another aspect, x is an integer from 8 to 11; in another aspect, x is an integer from 9 to 11; in another aspect, x is an integer from 10 to 11; in another aspect, x is 11; in another aspect, x is 10; in another aspect, x is 9; in another aspect, x is 8; in another aspect, x is 7; in another aspect, x is 6; in another aspect, x is 5; in another aspect, x is 4; in another aspect, x is 3; in another aspect, x is 2. In another aspect of these embodiments, R m4 It's methyl.
[0061] In one aspect of the copolymers of structure (A) described herein, L 1is a 1,4-phenylene spacer group, the repeating units of structure (I) are from about 23 mol % to about 48 mol %, the repeating units of structure (II) are from about 25 mol % to about 35 mol %, the repeating units of structure (III) are from about 15 mol % to about 45 mol %, the repeating units of structure (IV) are from about 2 to about 5 mol %, and the sum of the individual mole % of the repeating units of structures (I), (II), (III) and (IV) is equal to 100 mol % of the total repeating units in the copolymer.
[0062] In one aspect of the copolymers of structure (A) described herein, L 1 is a C-2 to C-12 alkylene spacer group, and the repeating unit of structure (IV) has structure (IVa).
[0063] In one aspect of the copolymers of structure (A) described herein, L 1 is a 1-4-phenylene spacer group, and the repeating unit of structure (IV) has structure (IVb).
[0064] In one aspect of the copolymers of structure (A) described herein, R m1 and R m2 It's H.
[0065] In one aspect of this embodiment of the copolymers of structure (A) described herein, R m3 It's H.
[0066] In one aspect of this embodiment of the copolymers of structure (A) described herein, R m4 It's H.
[0067] In one aspect of this embodiment of the copolymers of structure (A) described herein, R m3 is C-1 to C-4 alkyl. In a specific aspect of this embodiment, R m3 It's methyl.
[0068] In one aspect of this embodiment of the copolymers of structure (A) described herein, R m4 is C-1 to C-4 alkyl. In a specific aspect of this embodiment, R m4 It's methyl.
[0069] In one aspect of this embodiment of the copolymers of structure (A) described herein, R 1 It is a C-1 to C-4 alkyl group.
[0070] In one aspect of this embodiment of the copolymers of structure (A) described herein, R 1 It's H.
[0071] In one aspect of this embodiment of the copolymer of structure (A) described herein, the repeating unit of structure (I) has structure (la).
[0072] In one aspect of this embodiment of the copolymers of structure (A) described herein, R 2 It is a C-1 to C-4 alkyl group.
[0073] In one aspect of this embodiment of the copolymers of structure (A) described herein, R 2 is H. In another aspect of this embodiment, the repeating unit of structure (II) has structure (IIa),
[0074] In one aspect of this embodiment of the copolymers of structure (A) described herein, R 3 It is a C-1 to C-4 alkyl group.
[0075] In one aspect of this embodiment of the copolymers of structure (A) described herein, R 3 In another aspect of this embodiment, the repeating unit of structure (III) has structure (IIIa).
[0076] In one aspect of this embodiment of the copolymer of structure (A) described herein, the repeating unit of structure (IV) has structure (IVc).
[0077] In one aspect of this embodiment of the copolymer of structure (A) described herein, the repeating unit of structure (IV) has structure (IVd).
[0078]
[0079] In one aspect of this embodiment of the copolymer of structure (A) described herein, it has structure (A-1). In one aspect of this embodiment, Rr 1 In another aspect of this embodiment, R 2 is C-1 to C-8 alkyl. In another aspect of this embodiment, Rr 2 is a C-1 to C-8 alkylene hydroxyl moiety. In another aspect of this embodiment, R 2 is a C-1 to C-8 alkylene carboxylic acid. In another aspect of this embodiment, wherein R 2 is a moiety of structure (B) comprising benzyl alcohol; in another aspect of this embodiment, it has a more specific structure (B-1). In one aspect of this embodiment, Rr is a cyano moiety (-CN). In another aspect of this embodiment, Rr is a carbonylalkyl moiety (-C(=O)-Ri), wherein Ri is a C-1 to C-8 alkyl or aryl moiety.
[0080]
[0081]
[0082] In one aspect of this embodiment of the copolymer of structure (A) described herein, it has structure (A-2). In one aspect of this embodiment, Rr 1 In another aspect of this embodiment, R 2 is C-1 to C-8 alkyl. In another aspect of this embodiment, Rr 2 is a C-1 to C-8 alkylene hydroxyl moiety. In another aspect of this embodiment, R 2 is a C-1 to C-8 alkylene carboxylic acid. In another aspect of this embodiment, wherein R 2 is a moiety of structure (B) comprising benzyl alcohol; in another aspect of this embodiment, it has a more specific structure (B-1). In one aspect of this embodiment, Rr is a cyano moiety (-CN). In another aspect of this embodiment, Rr is a carbonylalkyl moiety (-C(=O)-Ri), wherein Ri is a C-1 to C-8 alkyl or aryl moiety.
[0083]
[0084] Another aspect of the present invention is a composition comprising any of the copolymer embodiments of the present invention having structure (A) described herein and an organic spin casting solvent.
[0085] Another aspect of the present invention is a composition comprising any of the copolymer embodiments of the present invention having structure (A) described herein and an organic spin casting solvent, wherein L 1 is a C-2 to C-12 alkylene spacer group.
[0086] Another aspect of the present invention is a composition comprising any of the copolymer embodiments of the present invention having structure (A) described herein and an organic spin casting solvent, wherein L 1 is a C-2 to C-12 alkylene spacer group, and Rr 2 It is a C-1 to C-8 alkyl group.
[0087] Another aspect of the present invention is a composition comprising any of the copolymer embodiments of the present invention having structure (A) described herein and an organic spin casting solvent, wherein L 1 is a C-2 to C-12 alkylene spacer group, and Rr 2 is a C-1 to C-8 alkylene hydroxyl moiety, a C-1 to C-8 alkylene carboxylic acid, or a structure (B) moiety containing benzyl alcohol.
[0088] Another aspect of the present invention is a composition comprising any of the copolymer embodiments of the present invention having structure (A) described herein and an organic spin casting solvent, wherein L 1 It is a 1-4-phenylene spacer group.
[0089] Another aspect of the present invention is a composition comprising any of the copolymer embodiments of the present invention having structure (A) described herein and an organic spin casting solvent, wherein L 1 is a 1-4-phenylene spacer group, and Rr 2 It is a C-1 to C-8 alkyl group.
[0090] Another aspect of the present invention is a composition comprising any of the copolymer embodiments of the present invention having structure (A) described herein and an organic spin casting solvent, wherein L 1 is a 1-4-phenylene spacer group, and Rr 2 is a C-1 to C-8 alkylene hydroxyl moiety, a C-1 to C-8 alkylene carboxylic acid, or a benzyl alcohol comprising a moiety of structure (B).
[0091] Spin-casting solvents for compositions comprising the copolymers of the present invention
[0092] Suitable solvents for use as organic spin casting solvents are any solvents for spin casting materials (e.g., photoresists, bottom anti-reflective coatings, or other types of organic coatings for photolithographic processing using semiconductor materials) that can dissolve the compounds of the present invention. There are no limiting examples. In another aspect of the novel composition, the organic spin casting solvent is an organic spin casting solvent that can dissolve the compounds of the present invention. This organic spin casting solvent can be a single solvent or a solvent mixture. Suitable solvents are organic solvents, which may include, for example, glycol ether derivatives such as ethyl cellosolve, methyl cellosolve, propylene glycol monomethyl ether (PGME), diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, dipropylene glycol dimethyl ether, propylene glycol n-propyl ether or diethylene glycol dimethyl ether; glycol ether ester derivatives such as ethyl cellosolve acetate, methyl cellosolve acetate or propylene glycol monomethyl ether acetate (PGMEA); carboxylic acid esters such as ethyl acetate, n-butyl acetate and amyl acetate; carboxylic acid esters of dibasic acids such as diethyl oxalate and diethyl malonate; dicarboxylic acid esters of glycols such as ethylene glycol diacetate and propylene glycol diacetate; and hydroxycarboxylic acid esters. , such as methyl lactate, ethyl lactate (EL), ethyl glycolate and ethyl 3-hydroxypropionate; ketoesters, such as methyl pyruvate or ethyl pyruvate; alkyloxycarboxylates, such as methyl 3-methoxypropionate, ethyl 3-ethoxypropionate, ethyl 2-hydroxy-2-methylpropionate or methyl ethoxypropionate; ketone derivatives, such as methyl ethyl ketone, acetylacetone, cyclopentanone, cyclohexanone or 2-heptanone; ketoether derivatives, such as diacetone alcohol methyl ether; ketoalcohol derivatives, such as acetone alcohol or diacetone alcohol; ketals or acetals, such as 1,3-dioxolane and diethoxypropane; lactones, such as butyrolactone; amide derivatives, such as dimethylacetamide or dimethylformamide, anisole, and mixtures thereof. In one aspect of this embodiment, the solvent may be PGMEA and a mixture of PGMEA and PGME. In one aspect of this embodiment, the solvent is PGMEA.
[0093] Methods of using the compositions of the present invention
[0094] Another aspect of the present invention is a method of forming a crosslinked or grafted and crosslinked coating of a copolymer comprising the steps of:
[0095] i) forming a coating on a substrate using any of the compositions described herein comprising a copolymer of structure (A),
[0096] ii) heating the coating at a temperature of about 90° C. to about 180° C. to remove the solvent and form a coating of a crosslinked or grafted and crosslinked copolymer,
[0097] iii) heating the crosslinked or grafted and crosslinked coating of step ii) from about 200°C to about 250°C to form a fully crosslinked or fully crosslinked and grafted copolymer coating.
[0098] Another aspect of the present invention is a method of forming a crosslinked or grafted and crosslinked neutral coating on a substrate, comprising the steps of:
[0099] ia) forming a coating on a substrate using any of the compositions described herein comprising a copolymer of structure (A),
[0100] iia) heating the coating at a temperature of about 90° C. to about 180° C. to remove the solvent and form a crosslinked or crosslinked and grafted coating,
[0101] iiia) heating the crosslinked coating of step iid) at a temperature of about 200° C. to about 250° C. to form a fully crosslinked or fully crosslinked and grafted neutral coating.
[0102] Another aspect of the present invention is a method of forming a cross-linked neutral coating on a substrate, comprising the steps of:
[0103] ib) forming a coating of any of the compositions described herein comprising a copolymer of structure (A) and an organic spin casting solvent on a substrate, wherein Rr 2 is a C-1 to C-8 alkyl group,
[0104] iib) heating the coating at a temperature of about 90° C. to about 180° C. to remove the solvent and form a crosslinked or grafted and crosslinked coating,
[0105] iiib) heating the crosslinked or grafted and crosslinked coating of step iif) at a temperature of about 200° C. to about 250° C. to form a fully crosslinked neutral coating.
[0106] Another aspect of the present invention is a method for forming a grafted and cross-linked neutral coating on a substrate, comprising the steps of:
[0107] ic) forming a coating comprising any of the compositions described herein comprising a copolymer of structure (A) and an organic spin casting solvent on a substrate, wherein Rr 2 is a C-1 to C-8 alkylene hydroxyl moiety, a C-1 to C-8 alkylene carboxylic acid, or a moiety of structure (B) comprising benzyl alcohol,
[0108] iic) heating the coating at a temperature of about 90° C. to about 180° C. to remove the solvent and form a grafted and crosslinked coating,
[0109] iiic) heating the crosslinked coating of step iic) at a temperature of about 200° C. to about 250° C. to form a completely grafted and crosslinked neutral coating.
[0110] Another aspect of the invention is a method for forming a self-assembling block copolymer coating on a neutral coating, comprising the steps of:
[0111] id) forming a neutral coating using any of the methods described herein, the method applying a composition comprising any of the copolymers of structure (A),
[0112] iid) applying a block copolymer onto the neutral coating and annealing until directed self-assembly of the block copolymer coating occurs.
[0113] Another aspect of the present invention is a method for pattern epitaxial directed self-assembly of a block copolymer coating for forming an image, comprising the steps of:
[0114] ie) forming a neutral coating using any of the methods described herein, the method applying a composition comprising any of the copolymers of structure (A),
[0115] iie) providing a coating of a photoresist coating on the neutral coating, and
[0116] forming a pattern in the photoresist coating,
[0117] iiie) applying a block copolymer comprising an etch-resistant block and a highly etchable block on the photoresist pattern and annealing until directed self-assembly occurs; and
[0118] The block copolymer is etched by etching the block copolymer, thereby removing the highly etchable blocks in the copolymer overcoat regions of the substrate and simultaneously forming a pattern in the substrate selectively in these regions.
[0119] In another aspect of the method, including steps ie) to ive), the pattern in the photoresist coating is formed by imaging lithography selected from electron beam, broadband, 193nm immersion, 193nm dry, 13.5nm, 248nm, 365nm and 436nm lithography.
[0120] Another aspect of the present invention is a method for chemical epitaxial directed self-assembly of a block copolymer coating for forming an image, comprising the steps of:
[0121] if) forming a neutral coating using any of the methods described herein using a composition comprising any of the copolymers of structure (A),
[0122] iif) providing a coating of a photoresist coating on the neutral coating, and
[0123] forming a pattern in the photoresist coating thereby forming areas where the neutral coating is not covered by the resist,
[0124] iiif) treating the uncovered neutral coating to remove it, forming a pinning area,
[0125] ivf) removing the photoresist to expose the unaffected neutral coating to form a chemical epitaxial pattern containing neutral and pinned regions,
[0126] vf) applying a block copolymer comprising an etch-resistant block and a highly etchable block over the neutral coating and annealing until directed self-assembly occurs; and
[0127] vif) etching the block copolymer, thereby removing the highly etchable blocks in the copolymer overcoat regions of the substrate and simultaneously forming a pattern in the substrate selectively in these regions.
[0128] In another aspect of the method, comprising steps if) to vif), the pattern in the photoresist coating is formed by imaging lithography selected from e-beam, broadband, 193nm immersion, 193nm dry, 13.5nm, 248nm, 365nm and 436nm lithography.
[0129] Another aspect of the present invention is the use of the random polymer having structure (A) described herein or the composition comprising the random polymer having structure (A) described herein for forming a coating on a substrate. Example
[0130] Chemicals and Characterization Equipment
[0131] Unless otherwise stated, chemicals were obtained from Millipore-Sigma (St. Louis, Missouri).
[0132] The SiARC used in these examples are JSR SiARC ISX-302 and JSR SiARC ISX-302ISX-304, which are available from JSR Micro, Inc. (1280 N. Mathilda Ave, Sunnyvale, CA 94089).
[0133] The spectrometer was used with a Bruker Advance III 400 MHz spectrometer (e.g., using CDCl 3 as solvent) 1 H NMR spectroscopy.
[0134] The photolithography experiment was completed using a TEL Clean ACT8 glue developer (track). The SEM images were taken using an Applied Materials NanoSEM_3D scanning electron microscope, and the images were displayed at 5 FOV magnification or 100 FOV magnification (field of view (FOV) = 5 μm, using 1, 2, 4 and 10 FOV).
[0135] Unless otherwise stated, molecular weight measurements (also referred to as M n polydispersity) is obtained by and The chromatography was performed on a gel permeation chromatograph (PSS Inc. Germany) with a μ-ultrastyragel column using THF solvent as the eluent. Polystyrene polymer standards were used for calibration. and GPC was measured using an Agilent gel permeation chromatography system with a μ-ultrastyragel column, which showed 1 st P(SDPE) block has M n (GPC) = 45,048 g / mol and M w / M n = 1.04, relative to PS calibration standard. Gel Permeation Chromatography: 0.1 μL of a 1 mg / mL THF solution was injected into a polystyrene calibrated GPC tool with a THF flow rate of 1 mL / min.
[0136] Synthesis of polymer materials for testing
[0137] Reference Block Copolymer Synthesis Example 1 Synthesis of P(Sb-MMA) (62k-b-25k)
[0138] P(Sb-MMA)(62K-b-25K) was synthesized using the same procedure as described in Example 2. In order to obtain the target Mn and the composition of PS and PMMA blocks, the amount of initiator and the number of monomers were changed. In short, 20 g (192 mmol) of styrene was polymerized using 4.38 mL (1.4 M solution) of sec-butyl lithium. Then, 0.07 g (0.38 mmol) of 1,1'-diphenylethylene (DPE) in 2.5 ml of anhydrous toluene was added to the reactor via an ampoule. The orange color of the reaction mixture turned dark brick red, indicating that the styryl lithium active center was converted into a delocalized DPE adduct carbon anion. After stirring for 2 minutes, a small amount (2 mL) of the reaction mixture was taken out for PS block molecular weight analysis. Methyl methacrylate (8.10 g, 81 mmol) was then added via an ampoule. After 30 min, the reaction was terminated with 1 mL of degassed methanol. The block copolymer was recovered by precipitation in excess isopropanol (5 times the polymer solution) containing 10% water, filtered, and vacuum dried at 55°C for 12 hours to obtain 26.5 g of P(Sb-MMA) (94% yield), which consisted of 70.1 mol% polystyrene blocks and 29.9 mol% polymethyl methacrylate blocks. The molecular weight of the diblock copolymer obtained by GPC was Mn,PS-b-PMMA=86518 g / mol and Mw / Mn=1.01.
[0139] Reference Block Copolymer Solution (Reference SOL 1)
[0140] Reference block copolymer synthesis example 1 was dissolved in PGMEA as a 1.7 wt % solution and filtered through a 0.2 micron PTFE filter. This solution was used to complete a neutral experiment to evaluate both the neutral layer of the present invention and the non-polar pinning layer of the present invention, as described below:
[0141] Summary of the neutral layer experimental results of the present invention
[0142] Specific examples of crosslinkable neutral tetrapolymers disclosed herein are found to be compatible with SiARC as well as SiOx, SiNyOx and SiN substrates. These new tetrapolymers are composed of styrene (S), 4-vinylbenzocyclobutene (VBCB), methyl methacrylate (MMA) and 2-hydroxyethyl methacrylate (HEMA) or 4-hydroxyphenyl methacrylate (PQMA), which are initiated by 2,2′-azobis(2-methylpropionitrile) (AIBN), 4,4′-azobis(4-cyanopentanol) (AIBN-OH) or 4,4′-azobis(4-cyanovaleric acid) (AIBN-COOH), and are prepared to address defectivity issues and problems found in neutral layers formed from terpolymers. The composition of NLD-175 was improved to P(Sr-VBCB-r-MMA-r-HEMA)-OH [i.e., hydroxyl terminated poly(styrene-co-4-vinylbenzocyclobutene-co-methyl methacrylate-co-2-hydroxyethyl methacrylate)] and P(Sr-VBCB-r-MMA-r-PQMA)-OH [i.e., hydroxyl terminated poly(styrene-co-4-vinylbenzocyclobutene-co-methyl methacrylate-co-4-hydroxyphenyl methacrylate)] to obtain a cross-linked neutral pad with low coating defects. The S component imparts the desired hydrophobicity to the polymer. The VBCB hydrophobic component allows the polymer to cross-link into an insoluble film when baked. The MMA component imparts the desired hydrophilicity to the polymer. The current results indicate that a %HEMA or %PQMA composition consisting of 1-5% imparts good compatibility to SiARC. The HEMA and PQMA components make the polymer more hydrophilic and compatible with SiARC substrates. When VBCB is crosslinked upon heating, the hydroxyl or carboxylic acid terminated end groups from the free radical initiator facilitate the grafting of the polymer chains to the substrate. These groups will contribute to the overall hydrophilicity of the polymer and may disrupt the neutrality of the membrane to the diblock copolymer.
[0143] For the analysis of the cross-linked film, the film retention was first checked with an immersion test and the neutrality was checked with a fingerprint test. The novel tetrapolymer solution was spin coated on a wafer and baked. This newly formed film was soaked in an EBR solvent and then rinsed off. Measurement of film thickness before and after the immersion test will determine the film retention. The diblock copolymer comparative example 1 was solution coated on a BCP (PME-979) and annealed on a novel tetrapolymer film to study the neutrality of the fingerprint appearance. This impartiality of either block of the diblock copolymer allows the BCP to self-assemble into contact holes. The coating was then analyzed for defects using an internal SEM, which showed an improved coating with no obvious defects.
[0144] Embodiment 1:
[0145] Synthesis of poly(styrene-co-4-vinylbenzocyclobutene-co-methyl methacrylate-co-2-hydroxyethyl methacrylate)-hydroxyl terminated (48 / 35 / 15 / 2 feed)
[0146] Styrene (22.62 g, 217 mmol), 4-vinylbenzocyclobutene (8.84 g, 67.9 mmol), methyl methacrylate (15.86 g, 15.8 mmol), 2-hydroxyethyl methacrylate (1.18 g, 0.91 mmol), 4,4′-azobis(4-cyanopentanol) (1.50 g, 5.96 mmol) and 2-butanone (75 g) were added to a flask and sparged with nitrogen for 30 minutes. The mixture was heated in an 85°C oil bath for 16 hours. The mixture was cooled to room temperature and diluted with THF and precipitated in IPA. The polymer was collected and redissolved in THF as a 15% solid solution and precipitated in IPA. The polymer was collected and dried in a vacuum oven. The polymer was dissolved in EtOAc as a 10% solid solution, washed four times with deionized water, and precipitated in IPA. The polymer was collected by vacuum filtration, air-dried, and dried overnight in a vacuum oven at 70°C. 24.1 g (50.0%) white powder, GPC: 11241 g / mol, Mn, 23167 g / mol, Mw, 2.06 PDI.
[0147] Embodiment 2:
[0148] Synthesis of poly(styrene-co-4-vinylbenzocyclobutene-co-methyl methacrylate-co-2-hydroxyethyl methacrylate)-hydroxyl terminated (33 / 30 / 35 / 2 feed)
[0149] Styrene (30.64 g, 294 mmol), 4-vinylbenzocyclobutene (34.82 g, 267 mmol), methyl methacrylate (31.24 g, 312 mmol), 2-hydroxyethyl methacrylate (2.32 g, 17.8 mmol), 4,4′-azobis(4-cyanopentanol) (0.99 g, 3.92 mmol), and 2-butanone (150 g) were added to a flask and bubbled with nitrogen for 30 minutes. The mixture was heated in an 85°C oil bath for 16 hours. The mixture was cooled to room temperature and diluted with THF and precipitated in IPA. The polymer was collected, redissolved in THF as a 15% solid solution, and precipitated in IPA. The polymer was collected and dried in a vacuum oven. The polymer was dissolved in EtOAc as a 10% solid solution, washed four times with deionized water, and precipitated in IPA. The polymer was collected by vacuum filtration, air-dried, and dried overnight in a vacuum oven at 70°C. 44.4 g (44.6%) white powder, GPC: 20225 g / mol, Mn, 46045 g / mol, Mw, 2.28 PDI.
[0150] Embodiment 3:
[0151] Synthesis of poly(styrene-co-4-vinylbenzocyclobutene-co-methyl methacrylate-co-2-hydroxyethyl methacrylate)-hydroxyl terminated (28 / 25 / 45 / 2 feed)
[0152] Styrene (26.40 g, 254 mmol), 4-vinylbenzocyclobutene (29.47 g, 226 mmol), methyl methacrylate (40.79 g, 407 mmol), 2-hydroxyethyl methacrylate (2.36 g, 18.1 mmol), 4,4′-azobis(4-cyanopentanol) (0.99 g, 3.92 mmol), and 2-butanone (150 g) were added to a flask and bubbled with nitrogen for 30 minutes. The mixture was heated in an 85°C oil bath for 16 hours. The mixture was cooled to room temperature, diluted with THF, and precipitated in IPA. The polymer was collected, redissolved in THF as a 15% solid solution, and precipitated in IPA. The polymer was collected and dried in a vacuum oven. The polymer was dissolved in EtOAc as a 10% solid solution, washed four times with deionized water, and precipitated in IPA. The polymer was collected by vacuum filtration, air-dried, and dried overnight in a vacuum oven at 70°C. 47.3 g (47.5%) white powder, GPC: 21644 g / mol, Mn, 46731 g / mol, Mw, 2.16 PDI.
[0153] Embodiment 4:
[0154] Synthesis of poly(styrene-co-4-vinylbenzocyclobutene-co-methyl methacrylate-co-2-hydroxyethyl methacrylate)-hydroxyl terminated (13 / 30 / 55 / 2 feed)
[0155] Styrene (6.07 g, 58.3 mmol), 4-vinylbenzocyclobutene (17.52 g, 135 mmol), methyl methacrylate (24.70 g, 247 mmol), 2-hydroxyethyl methacrylate (1.17 g, 0.90 mmol), 4,4′-azobis(4-cyanopentanol) (0.54 g, 2.16 mmol), and 2-butanone (75 g) were added to a flask and bubbled with nitrogen for 30 minutes. The mixture was heated in an 85°C oil bath for 16 hours. The mixture was cooled to room temperature, diluted with THF, and precipitated in IPA. The polymer was collected, redissolved in THF as a 15% solid solution, and precipitated in IPA. The polymer was collected and dried in a vacuum oven. The polymer was dissolved in EtOAc as a 10% solid solution, washed four times with deionized water, and precipitated in IPA. The polymer was collected by vacuum filtration, dried in air, and dried in a vacuum oven at 70°C overnight. 24.3 g (48.8%) white powder, GPC: 26761 g / mol, Mn, 43866 g / mol, Mw, 1.64 PDI.
[0156] Embodiment 5:
[0157] Synthesis of poly(styrene-co-4-vinylbenzocyclobutene-co-methyl methacrylate-co-4-hydroxyphenyl methacrylate)-hydroxyl terminated (48 / 35 / 15 / 2 feed)
[0158] Styrene (43.37 g, 416 mmol), 4-vinylbenzocyclobutene (39.53 g, 304 mmol), methyl methacrylate (13.03 g, 130 mmol), 4-hydroxyphenyl methacrylate (3.09 g, 17.3 mmol), 4,4′-azobis(4-cyanopentanol) (0.99 g, 3.92 mmol), and 2-butanone (150 g) were added to a flask and bubbled with nitrogen for 30 minutes. The mixture was heated in an 85°C oil bath for 16 hours. The mixture was cooled to room temperature, diluted with THF, and precipitated in IPA. The polymer was collected, redissolved in THF as a 15% solid solution, and precipitated in IPA. The polymer was collected and dried in a vacuum oven. The polymer was dissolved in EtOAc as a 10% solid solution, washed four times with deionized water, and precipitated in IPA. The polymer was collected by vacuum filtration, air-dried, and dried in a vacuum oven at 70°C overnight. 38.4 g (38.6%) white powder, GPC: 22482 g / mol, Mn, 40376 g / mol, Mw, 1.80 PDI.
[0159] Embodiment 6:
[0160] Synthesis of poly(styrene-co-4-vinylbenzocyclobutene-co-methyl methacrylate-co-4-hydroxyphenyl methacrylate)-hydroxyl terminated (33 / 30 / 35 / 2 feed)
[0161] Styrene (30.22 g, 290 mmol), 4-vinylbenzocyclobutene (34.35 g, 264 mmol), methyl methacrylate (30.82 g, 308 mmol), 4-hydroxyphenyl methacrylate (3.13 g, 17.6 mmol), 4,4′-azobis(4-cyanopentanol) (1.48 g, 5.86 mmol), and 2-butanone (150 g) were added to a flask and bubbled with nitrogen for 30 minutes. The mixture was heated in an 85°C oil bath for 16 hours. The mixture was cooled to room temperature, diluted with THF, and precipitated in IPA. The polymer was collected, redissolved in THF as a 15% solid solution, and precipitated in IPA. The polymer was collected and dried in a vacuum oven. The polymer was dissolved in EtOAc as a 10% solid solution, washed four times with deionized water, and precipitated in IPA. The polymer was collected by vacuum filtration, air-dried, and dried overnight in a vacuum oven at 70°C. 48.6 g (48.9%) white powder, GPC: 21056 g / mol, Mn, 37204 g / mol, Mw, 1.77 PDI.
[0162] Embodiment 7:
[0163] Synthesis of poly(styrene-co-4-vinylbenzocyclobutene-co-methyl methacrylate-co-4-hydroxyphenyl methacrylate)-hydroxyl terminated (30 / 30 / 35 / 5 feed)
[0164] Styrene (26.94 g, 259 mmol), 4-vinylbenzocyclobutene (33.68 g, 259 mmol), methyl methacrylate (30.22 g, 302 mmol), 4-hydroxyphenyl methacrylate (7.68 g, 43.1 mmol), 4,4′-azobis(4-cyanopentanol) (1.48 g, 5.86 mmol), and 2-butanone (150 g) were added to a flask and bubbled with nitrogen for 30 minutes. The mixture was heated in an 85°C oil bath for 16 hours. The mixture was cooled to room temperature, diluted with THF, and precipitated in IPA. The polymer was collected, redissolved in THF as a 15% solid solution, and precipitated in IPA. The polymer was collected and dried in a vacuum oven. The polymer was dissolved in EtOAc as a 10% solid solution, washed four times with deionized water, and precipitated in IPA. The polymer was collected by vacuum filtration, air-dried, and dried overnight in a vacuum oven at 70°C. 51.0 g (51.4%) white powder, GPC: 23315 g / mol, Mn, 38666 g / mol, Mw, 1.66 PDI.
[0165] Embodiment 8:
[0166] Synthesis of poly(styrene-co-4-vinylbenzocyclobutene-co-methyl methacrylate-co-4-hydroxyphenyl methacrylate)-hydroxyl terminated (23 / 30 / 45 / 2 feed)
[0167] Styrene (10.57 g, 102 mmol), 4-vinylbenzocyclobutene (17.24 g, 132 mmol), methyl methacrylate (19.88 g, 199 mmol), 4-hydroxyphenyl methacrylate (1.57 g, 8.8 mmol), 4,4′-azobis(4-cyanopentanol) (0.74 g, 2.93 mmol), and 2-butanone (75 g) were added to a flask and sparged with nitrogen for 30 minutes. The mixture was heated in an 85°C oil bath for 16 hours. The mixture was cooled to room temperature, diluted with THF, and precipitated in IPA. The polymer was collected, redissolved in THF as a 15% solid solution, and precipitated in IPA. The polymer was collected and dried in a vacuum oven. The polymer was dissolved in EtOAc as a 10% solid solution, washed four times with deionized water, and precipitated in IPA. The polymer was collected by vacuum filtration, air-dried, and dried overnight in a vacuum oven at 70°C. 24.9 g (50.1%) white powder, GPC: 20979 g / mol, Mn, 35723 g / mol, Mw, 1.70 PDI.
[0168] Comparative Example 1:
[0169] Synthesis of poly(styrene-co-4-vinylbenzocyclobutene-co-methyl methacrylate)-hydroxyl terminated (30 / 30 / 40 feed)
[0170] Styrene (28.0 g, 0.27 mol), 4-vinylbenzocyclobutene (35.0 g, 0.27 mol), methyl methacrylate (35.9 g, 0.36 mol), 4,4′-azobis(4-cyanopentanol) (0.99 g, 3.92 mmol) and 2-butanone (150 g) were added to a flask and bubbled with nitrogen for 30 minutes. The mixture was heated in an 85°C oil bath for 16 hours. The mixture was cooled to room temperature, diluted twice with THF, and then precipitated in isopropanol. The polymer was collected, redissolved in THF as a 15% solid solution, and precipitated in isopropanol. The polymer was collected and dried in vacuo at 70°C. 26 g (26%) white powder, GPC: 26113 g / mol, Mn, 43631 g / mol, Mw, 1.67 PDI.
[0171] Characterization
[0172] Table 1: gives a summary of the polymer properties of the polymers prepared in Examples 1-8. Figure 1 A representative example of the H-1 NMR spectrum of a hydroxyl terminated poly(styrene-co-4-vinylbenzocyclobutene-co-methyl methacrylate-co-4-hydroxyphenyl methacrylate) [P(Sr-VBCB-r-MMA-r-HEMA)-OH] polymer (Example 1) is shown. Figure 2 Representative examples of NMR spectra of poly(styrene-co-4-vinylbenzocyclobutene-co-methyl methacrylate-co-4-hydroxyphenyl methacrylate)-hydroxyl terminated [P(Sr-VBCB-r-MMA-r-PQMA)-OH] polymer (Example 5) are shown respectively.
[0173] Table 1
[0174]
[0175]
[0176] Coating and self-assembly results on SiARC:
[0177] SiARC coating
[0178] The coating of JSR SiARC ISX-302 or ISX-304 was prepared by coating on silicon wafers and 2 The wafer was baked at 220°C for 90 seconds. The wafer was divided into smaller coupons and bonded to a Si wafer.
[0179] Preparation and application of neutral layer test formulations:
[0180] Test solutions were prepared by dissolving the polymers of Examples 1 to 8 and Comparative Example 1 individually in PGMEA as 0.3 wt% solutions and filtering these through a 0.2 micron PTFE filter. These solutions were coated on SiARC substrates (either JSR SiARC ISX-302 and ISX-304) and baked at 250°C for 2 minutes in N2, SOL 1 (BCP) was coated and baked at 260°C for 15 minutes in air. The naming of the solutions reflects the naming of the examples, so SOL 1 to SOL8 are solutions formed from Examples 1 to 8, and SOL COMP 1 is a sample formed from Comparative Example 1.
[0181] Figure 3 The novel pads are shown coated on JSR SiARC ISX-302 and ISX-304. Clearly, dewetting defects were observed in the neutral layer films of SOL COMP 1 formed on both SiARCs. In contrast, unexpectedly, these coating defects were not observed for the inventive neutral layer films coated from SOL 1 and SOL 8, which were formulated with the inventive neutral layer polymers, respectively, comprising HEMA or PQMA as hydroxyl functionalized repeating units, prepared from AIBN-OH producing OH end groups.
[0182] The samples were evaluated using SEM tools for coating defects such as dewetting spots, black spots or white spots, such as Figure 4 As shown. SEM images with white spots are evaluated as dewetting defects. SEM images with light white spots are evaluated as slight defects. SEM images with almost inconspicuous white spots are evaluated as very slight defects. SEM images with no obvious spots are evaluated as no defects.
[0183] Similarly, Figure 5 It is shown that when the block copolymer coating results from coating of reference SOL 1 and annealing on a neutral pad coated on JSR SiARC ISX-302, collapse of the self-assembled morphology is only observed on the comparative neutral layer coated from SOL COMP 1, while surprisingly, no collapse of the self-assembled morphology is observed on the neutral coatings on JSR SiARC ISX-302 formed from the inventive polymers in SOL 1 and SOL 5, respectively.
[0184] Figure 6 Evaluations showing SEM images with >90% contact hole morphology were rated as good C / H (A). SEM images with 50-89% contact hole morphology were rated as partial C / H (B). SEM images with 0-49% contact hole morphology were rated as poor C / H (C).
[0185] Figure 7 It is shown that when the block copolymer coating results were coated from reference SOL 1 and annealed on a neutral pad coated on JSR SiARC ISX-304, the self-assembled morphology observed was comparable between SOL COMP 1 and neutral coatings on JSR SiARC ISX-304 formed from the inventive polymers in SOL 1 and SOL 5, respectively.
[0186] Although the disclosed and claimed subject matter has been described and illustrated with a certain degree of particularity, it should be understood that it has been disclosed by way of example only and that those skilled in the art may make various changes in conditions and sequence of steps without departing from the spirit and scope of the disclosed and claimed subject matter.
Claims
1. A random polymer having structure (A), comprising The styrene repeating unit of structure (I), wherein R m1 is H or C-1 to C-4 alkyl, R 1 selected from H, C-1 to C-8 alkyl and C-1 to C-4 alkyloxy, n1 is the total number of such repeating units; wherein in the copolymer, such repeating units are in the range of about 10 mol% to about 60 mol%; The repeating unit derived from 4-vinylbenzocyclobutene of structure (II) wherein R m2 is H or C-1 to C-4 alkyl, R 2 is H or C-1 to C-8 alkyl, and n2 is the total number of such repeating units; wherein in the copolymer, such repeating units are from about 15 mol% to about 35 mol%; The repeating unit derived from an alkyl acrylate or 2-methylene alkanoate of structure (III), wherein R m3 is H or C-1 to C-4 alkyl, R 3 is a C-1 to C-8 alkyl group, and n3 is the total number of repeating units; wherein in the copolymer, the repeating unit is about 15 mol% to about 55 mol%; The repeating unit derived from a hydroxy-substituted acrylate or 2-methylene alkanoate of structure (IV), wherein R m4 is H or C-1 to C-4 alkyl, R I is a C-1 to C-8 alkyl group, L 1 is a spacer moiety selected from a C-2 to C-12 alkylene spacer and a 1,4-phenylene spacer, wherein the alkylene spacer is selected from a C-2 to C-12 straight chain alkylene, a C-3 to C-12 branched chain alkylene, a C-3 to C-12 cyclic alkylene, and a C-5 to C-12 alicyclic alkylene, wherein there are at least two carbon atoms between the carbonyloxy moiety and the OH moiety, and the two moieties are independently attached to the alkylene spacer at different positions, the different positions being primary or secondary carbons on the alkylene moiety, and wherein the 1,4-phenylene spacer is a spacer in which the carboxyloxy moiety and the OH moiety are located at 1,4 positions relative to each other, and n4 is the total number of repeating units; wherein in the copolymer, this repeating unit is from about 1 mol% to about 5 mol%; The two terminal groups shown in structure (A) are H and Rr, Rr 1 and Rr 2 A substituted methyl moiety, wherein Rr 1 is a C-1 to C-8 alkyl group, Rr 2 selected from C-1 to C-8 alkyl, C-1 to C-8 alkylene hydroxyl moiety (-alkylene-OH), C-1 to C-8 alkylene carboxylic acid moiety (-alkylene-CO 2 H), or a moiety of structure (B) comprising benzyl alcohol, wherein ni is an integer in the range of 0 to 5, nia is an integer in the range of 1 to 5, nib is an integer in the range of 1 to 5, and "*" indicates the point of attachment of this moiety, Rr is a cyano moiety (-CN) or a carbonylalkyl moiety (-C(=O)-Ri), wherein Ri is a C-1 to C-8 alkyl or aryl moiety, and further wherein the sum of the individual mole % of repeating units of structures (I), (II), (III) and (IV) is less than or equal to 100 mole % of the total repeating units present in the copolymer:
2. The copolymer according to claim 1, which consists of the repeating units of structures (I), (II), (III) and (IV), wherein the sum of these repeating units is 100 mol%.
3. The copolymer according to claim 1 or 2, wherein L 1 is the C-2 to C-12 alkylene spacer group.
4. The copolymer according to claim 1 or 2, wherein L 1 is the 1,4-phenylene moiety spacer group.
5. The copolymer according to any one of claims 1 to 3, wherein The repeating unit of structure (I) is about 13 mol % to about 48 mol %, The repeating unit of structure (II) is about 25 mol % to about 35 mol %, The repeating unit of structure (III) is about 15 mol % to about 55 mol %, The repeating unit of structure (IV) is about 1 mol % to about 2 mol %, and L 1 is the C-2 to C-12 alkylene spacer group, and the sum of the individual mole % of the repeating units of structures (I), (II), (III) and (IV) is equal to 100 mole % of the total repeating units in the copolymer.
6. The copolymer according to any one of claims 1 to 2 and 4, wherein The repeating unit of structure (I) is about 23 mol % to about 48 mol %, The repeating unit of structure (II) is about 25 mol % to about 35 mol %, The repeating unit of structure (III) is about 15 mol % to about 45 mol %, The repeating unit of structure (IV) is from about 2 to about 5 mol %, and L 1 is a 1,4-phenylene spacer group, and further wherein the sum of the individual mole % of the repeating units of structures (I), (II), (III) and (IV) equals 100 mole % of the total repeating units in the copolymer.
7. The copolymer according to any one of claims 1 to 6, wherein in the repeating unit of structure (IV), L 1 is the alkylene spacer group and is selected from Structure (IVa1), Structure (IVa2), Structure (IVa3), Structure (IVa4) or Structure (IVa5), wherein x is an integer from 1 to 11, x1 is an integer from 1 to 8, x2 is an integer from 1 to 8, x3 is an integer from 1 to 2, x3a is an integer from 1 to 3, R x1 is a C-1 to C-4 alkyl group, R x2 is a C-1 to C-4 alkyl group, and in the repeating unit of structure (IVa5), the substituent R x4 or R x5 only one of them is OH, wherein further the remaining substituents in the repeating unit of structure (IVa5) are H, The copolymer according to claim 7 , wherein the repeating unit of structure (IV) has structure (IVa1).
9. The copolymer according to claim 7, wherein the repeating unit of structure (IV) has structure (IVa2). 10 . The copolymer according to claim 7 , wherein the repeating unit of structure (IV) has structure (IVa3).
11. The copolymer according to claim 7, wherein the repeating unit of structure (IV) has structure (IVa4).
12. The copolymer according to claim 7 or 11, wherein the repeating unit of structure (IV) has structure (IVa41), 13. The copolymer according to claim 7 or 11, wherein the repeating unit of structure (IV) has structure (IVa42), 14. The copolymer according to claim 7 or 11, wherein the repeating unit of structure (IV) has structure (IVa43), 15. The copolymer according to claim 7, wherein the repeating unit of structure (IV) has structure (IVa5).
16. The copolymer according to claim 14, wherein the repeating unit of structure (IV) has structure (IVa51) or structure (IVa52), 17. The copolymer according to any one of claims 1 to 5, 7 and 8, wherein the repeating unit of structure (IV) has structure (IVa), 18. The copolymer according to any one of claims 1 to 4 and 6, wherein the repeating unit of structure (IV) has structure (IVb), 19. The copolymer according to any one of claims 1 to 18, wherein R m1 and R m2 It's H.
20. The copolymer according to any one of claims 1 to 19, wherein R m3 It's H.
21. The copolymer according to any one of claims 1 to 20, wherein R m4 It's H.
22. The copolymer according to any one of claims 1 to 19 and 21, wherein R m3 It is a C-1 to C-4 alkyl group.
23. The copolymer according to any one of claims 1 to 20 and 22, wherein R m4 It is a C-1 to C-4 alkyl group.
24. The copolymer according to any one of claims 1 to 19, 21 and 23, wherein R m3 It's methyl.
25. The copolymer according to any one of claims 1 to 20, 22 to 24, wherein R m4 It's methyl.
26. The copolymer according to any one of claims 1 to 25, wherein R 1 It is a C-1 to C-4 alkyl group.
27. The copolymer according to any one of claims 1 to 25, wherein R 1 It's H.
28. The copolymer of claim 27, wherein the repeating unit of structure (I) has structure (Ia), 29. The copolymer according to any one of claims 1 to 28, wherein R 2 It is a C-1 to C-4 alkyl group.
30. The copolymer according to any one of claims 1 to 29, wherein R 2 It's H.
31. The copolymer of claim 30, wherein the repeating unit of structure (II) has structure (IIa), 32. The copolymer according to any one of claims 1 to 31, wherein R 3 It is a C-1 to C-4 alkyl group.
33. The copolymer according to any one of claims 1 to 32, wherein R 3 It's methyl.
34. The copolymer of claim 33, wherein the repeating unit of structure (III) has structure (IIIa), 35. The copolymer according to any one of claims 1 to 5, 7 and 28 to 34, wherein the repeating unit of structure (IV) has structure (IVc), 36. The copolymer of any one of claims 1 to 4, 6 and 28 to 34, wherein the repeating unit of structure (IV) has structure (IVd), 37. The copolymer according to any one of claims 1 to 5, 7 and 28 to 34, wherein the copolymer has structure (A-1), 38. The copolymer of claim 37, wherein Rr 1 It's methyl.
39. The copolymer according to claim 37 or 38, wherein Rr 2 It is a C-1 to C-8 alkyl group.
40. The copolymer according to claim 37 or 38, wherein Rr 2 is a C-1 to C-8 alkylene hydroxy moiety.
41. The copolymer according to claim 37 or 38, wherein Rr 2 It is a C-1 to C-8 alkylene carboxylic acid.
42. The copolymer according to claim 37 or 38, wherein Rr 2 is the moiety of structure (B) comprising benzyl alcohol.
43. The copolymer of claim 42, wherein structure (B) has structure (B-1), 44. The copolymer of any one of claims 37 to 43, wherein Rr is a cyano moiety (-CN).
45. The copolymer of any one of claims 37 to 43, wherein Rr is a carbonylalkyl moiety (-C(=O)-Ri), wherein Ri is a C-1 to C-8 alkyl or aryl moiety.
46. The copolymer according to any one of claims 1 to 4, 6, 28 to 34 and 36, wherein the copolymer has structure (A-2), 47. The copolymer of claim 46, wherein Rr 1 It's methyl.
48. The copolymer according to claim 46 or 47, wherein Rr 2 It is a C-1 to C-8 alkyl group.
49. The copolymer according to claim 46 or 47, wherein Rr 2 is a C-1 to C-8 alkylene hydroxy moiety.
50. The copolymer according to claim 46 or 47, wherein Rr 2 It is a C-1 to C-8 alkylene carboxylic acid.
51. The copolymer according to claim 46 or 47, wherein Rr 2 is the moiety of structure (B) comprising benzyl alcohol.
52. The copolymer of claim 51, wherein structure (B) has structure (B-1), 53. The copolymer of any one of claims 46 to 52, wherein Rr is a cyano moiety (-CN).
54. The copolymer of any one of claims 46 to 52, wherein Rr is a carbonylalkyl moiety (-C(=O)-Ri), wherein Ri is a C-1 to C-8 alkyl or aryl moiety.
55. A composition comprising the copolymer of any one of claims 1 to 54 and an organic spin casting solvent.
56. according to the composition described in claim 55, wherein in described copolymer, L 1 is the alkylene spacer group.
57. according to the composition described in claim 55, wherein in described copolymer, L 1 is the alkylene group, and further wherein Rr 2 is the C-1 to C-8 alkyl group.
58. according to the composition described in claim 55, wherein in described copolymer, L 1 is the alkylene group, and further wherein Rr 2 selected from C-1 to C-8 alkylene hydroxyl moieties (-alkylene-OH), C-1 to C-8 alkylene carboxylic acid moieties (-alkylene-CO 2 H) and a moiety of structure (B) comprising benzyl alcohol.
59. according to the composition described in claim 55, wherein in described copolymer, L 1 is the 1,4-phenylene spacer group.
60. according to the composition described in claim 55, wherein in described copolymer, L 1 is the 1,4-phenylene spacer group, and further wherein Rr 2 is the C-1 to C-8 alkyl group.
61. according to the composition described in claim 55, wherein in described copolymer, L 1 is the 1,4-phenylene spacer group, and further wherein Rr 2 selected from C-1 to C-8 alkylene hydroxyl moieties (-alkylene-OH), C-1 to C-8 alkylene carboxylic acid moieties (-alkylene-CO 2 H) and a moiety of structure (B) comprising benzyl alcohol.
62. A method for forming a crosslinked or grafted and crosslinked copolymer coating on a substrate, wherein The following steps are involved: i) forming a coating of the composition according to any one of claims 55 to 61 on a substrate, ii) heating the coating at a temperature of about 90° C. to about 180° C. to remove the solvent and form a crosslinked or grafted and crosslinked coating of the copolymer, iii) heating the crosslinked or grafted and crosslinked coating of step ii) from about 200° C. to about 250° C. to form a fully crosslinked or fully crosslinked and grafted copolymer coating.
63. A method for forming a crosslinked or grafted and crosslinked neutral coating on a substrate, wherein The following steps are involved: ia) forming a coating of the composition according to any one of claims 55 to 61 on a substrate, iia) heating the coating at a temperature of about 90° C. to about 180° C. to remove the solvent and form a crosslinked or grafted and crosslinked coating, iiia) heating the crosslinked coating of step iid) at a temperature of about 200° C. to about 250° C. to form a fully crosslinked neutral coating.
64. A method for forming a cross-linked neutral coating on a substrate, wherein The following steps are involved: ib) forming a coating of the composition according to claim 57 or 60 on a substrate, iib) heating the coating at a temperature of about 90° C. to about 180° C. to remove the solvent and form a crosslinked or grafted and crosslinked coating, iiib) heating the crosslinked or grafted and crosslinked coating of step iif) at a temperature of about 200° C. to about 250° C. to form a fully crosslinked neutral coating.
65. A method for forming a grafted and cross-linked neutral coating on a substrate, wherein The following steps are involved: ic) forming a coating of the composition according to claim 58 or 61 on a substrate, iic) heating the coating at a temperature of about 90° C. to about 180° C. to remove the solvent and form a grafted and crosslinked coating, iiic) heating the crosslinked coating of step iic) at a temperature of about 200° C. to about 250° C. to form a fully grafted and crosslinked neutral coating.
66. A method for forming a self-assembled block copolymer coating on a neutral coating, wherein The following steps are involved: id) forming a neutral coating according to any one of claims 62 to 65, iid) applying a block copolymer onto the neutral coating and annealing until directed self-assembly of the block copolymer coating occurs.
67. A method for pattern epitaxial directed self-assembly of a block copolymer coating for forming an image, wherein The following steps are involved: ie) forming a neutral coating according to any one of claims 62 to 65, iie) providing a coating of a photoresist coating on said neutral coating, and forming a pattern in the photoresist coating, iiie) applying a block copolymer comprising an etch-resistant block and a highly etchable block on the photoresist pattern and annealing until directed self-assembly occurs; and, ive) to etch the block copolymer, thereby removing the highly etchable blocks in the copolymer overcoat regions of the substrate and simultaneously forming a pattern in the substrate selectively in these regions.
68. The method of claim 67, wherein the pattern in the photoresist coating is formed by imaging lithography selected from the group consisting of e-beam, broadband, 193 nm immersion, 193 nm dry, 13.5 nm, 248 nm, 365 nm, and 436 nm lithography.
69. A method for chemical epitaxial directed self-assembly of block copolymer coatings for forming images, The following steps are involved: if) forming a neutral coating on a substrate according to any one of claims 62 to 65, iif) providing a coating of a photoresist coating on said neutral coating, and forming a pattern in the photoresist coating thereby forming areas where the neutral coating is not covered by the resist, iiif) treating the uncovered neutral coating to remove it, forming a pinning area, ivf) removing the photoresist to expose the unaffected neutral coating to form a chemical epitaxial pattern containing neutral and pinned regions, vf) applying a block copolymer comprising an etch-resistant block and a highly etchable block on the neutral coating and annealing until directed self-assembly occurs; and vif) etching the block copolymer, thereby removing the highly etchable blocks in the copolymer overcoat regions of the substrate and simultaneously forming a pattern in the substrate selectively in these regions.
70. The method of claim 69, wherein the pattern in the photoresist coating is formed by imaging lithography selected from the group consisting of e-beam, broadband, 193 nm immersion, 193 nm dry, 13.5 nm, 248 nm, 365 nm, and 436 nm lithography.
71. Use of a random polymer according to any one of claims 1 to 54 or a composition according to any one of claims 55 to 61 for forming a coating on a substrate.
